Volatility-based adjustments to portfolio risk assessment tools - S. V. Korzhnev (Вестник университета, 2023)
The article is devoted to the analysis of correlation between assets in the Russian stock market. The purpose of the study is to assess the stability of correlation coefficients. The results of the Jennrich test and correlation analysis carried out indicate that correlation coefficients differ significantly for different volatility levels, that is, the coefficients in times of high volatility are significantly higher than those in times of low volatility. Correlations during periods of heightened volatility are key for assessing risks, since it is such volatility that characterizes negative market movements. The use of conventional correlation coefficients leads to an overestimation of the role of diversification in reducing the volatility in a portfolio of Russian assets and thus an underestimation of the investment portfolio risks. Risks can be assessed more accurately if correlation coefficients corresponding to periods of high volatility are used.